Quantitation of postantibiotic effect by measuring CO2 generation of bacteria with the BACTEC blood culture system. - Gottfredsson, M (1991)
The duration of the postantibiotic effect (PAE) determined by bacterial CO2 production measured by using the BACTEC NR 730 blood culture system was compared with PAEs determined by standard viability counting. PAEs for Staphylococcus aureus after exposure to dicloxacillin, vancomycin, rifampin, gentamicin, and ciprofloxacin and for Escherichia coli after exposure to ampicillin, gentamicin, and ciprofloxacin were quantitated by the two methods, and an excellent correlation (r = 0.93) was demonstrated. The difference in the PAE durations determined by the two methods was 0.1 +/- 0.4 (mean +/- standard deviation) h. Thus, the BACTEC CO2 generation method provides a simple, alternate way of determining the PAE in vitro.